2017
DOI: 10.4078/jrd.2017.24.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-homocysteinemia Inducing Hyperuricemia: What are the Mechanisms?

Abstract: Hyperuricemia is related to metabolic syndrome, and is defined as an over-production or under-excretion of uric acid (UA), with increased UA serum concentration. Among other causes, Hyper-homocysteinemia (H-Hcy) can be responsible for hyperuricemia. The mechanisms underlying the association between these two conditions are unclear, but increased UA serum levels can be a consequence of renovascular atherosclerosis, with reduced UA excretion. An alternative hypothesis is the overproduction of UA from adenosine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Hypertension was equally distributed between males and females (65% [16] and 75% [9] , respectively). The prevalence of smoking was 46% [17] ; with 55% [18] and 17% [2] in males and females, respectively. Further analyses revealed lower HCY level in males (12.99±4.22 µmol/L) compared to females (16.94±5.30 µmol/L) (p=0.042).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Hypertension was equally distributed between males and females (65% [16] and 75% [9] , respectively). The prevalence of smoking was 46% [17] ; with 55% [18] and 17% [2] in males and females, respectively. Further analyses revealed lower HCY level in males (12.99±4.22 µmol/L) compared to females (16.94±5.30 µmol/L) (p=0.042).…”
Section: Resultsmentioning
confidence: 94%
“…Contradictory results may be due to different selection of research participants, i.e. different inclusion and exclusion criteria in the study, different number of participants, methods used, genetic basis and different eating habits [17] . Genetic basis, sufficient intake of vitamins B6, B12 and folic acid, as well as preserved renal function, are factors that directly affect HCY level [11] and should all be considered during assessment in any case.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between hyperhomocysteinemia and uric acid is explained by the methioninehomocysteine cycle [25]. In this cycle, methionine is converted to S-adenosyl-homocysteine (SAH), which becomes Hcy and adenosine, with adenosine then being degraded to uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…1 Uric acid is the end product of purine metabolism and it has been considered protective against oxidative stress acting as an antioxidant. 3,4 A possible association between serum uric acid level and bone metabolism has been suggested. 3,4 A possible association between serum uric acid level and bone metabolism has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…2 It has been demonstrated that uric acid level and gout are risk factors for certain conditions or act as protective factors against various medical conditions. 3,4 A possible association between serum uric acid level and bone metabolism has been suggested. 5 A meta-analysis showed that subjects with higher serum uric acid levels had significantly higher bone mineral density (BMD) values for the spine and femur neck (FN).…”
Section: Introductionmentioning
confidence: 99%